Albania : 2010 Article IV Consultation; Staff Report; Staff Statement; Public Information on the Executive Board Discussion; and Statement by the Executive Director for Albania. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
Albania enjoyed strong growth with comparatively benign external vulnerabilities before the crisis. Monetary policy provided timely support, and the exchange rate functioned as a shock absorber. However, policy buffers are now exhausted and must be rebuilt. Fiscal tightening has to be quickly effected. Medium-term fiscal policy should be governed by a credible and monitorable fiscal rule. The Albanian economy has to broaden its sources of growth and strengthen competitiveness. Sound macroeconomic statistics are essential for competent policy making and investor confidence.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet